Modelling of metal oxide surge arresters as elements of overvoltage protection systems - Furgał, Jakub; Dau, Saad Khalifa Omar (My University, 2008)
Ograniczniki przepięć są powszechnie stosowane do ochrony przepięciowej urządzeń elektrycznych wysokiego i niskiego napięcia. Modele matematyczne ograniczników powinny właściwie odzwierciedlać charakterystyki napięciowo-prądowe warystorów podczas oddziaływania przepięć. Spośród wielu modeli opracowanych dotychczas do symulacji komputerowych zależności napięciowo-prądowych wybrano jeden model ograniczników. Parametry elementów modelu wyznaczono przy wykorzystaniu danych katalogowych. Modelowano zależności napięciowo-prądowe dla różnych udarów prądowych ogranicznika przepięć stosowanego w układach elektroenergetycznych 110 kV. Obliczenia porównano z wynikami badań.

Metal oxide surge arresters are used for protection of high and low voltage electric devices against overvoltages. Mathematical models of surge arresters should properly represent current-voltage dependencies of varistors during influence overvoltages. From among numerous models created so for two versions of a selected model were used for computer simulations of current-voltage dependences of surge arresters. Parameters of elements of the selected model can be calculated by use of data published in the catalogues. Current-voltage dependencies of the surge arrester designed for electric power systems of 110 kV for different current stroke were modelled. The results of computer simulations were compared with the experimental data.
Modelowanie ograniczników przepięć z tlenków metali jako elementów systemów ochrony przepięciowej
Elektrotechnika i Elektronika
Keywords: surge arresters; ograniczniki przepięć; mathematical modelling; symulacje komputerowe